Compositional Variation of Eudialyte-Group Minerals from the Lovozero and Ilímaussaq Complexes and on the Origin of Peralkaline Systems - Lia N. Kogarko; Troels F. D. Nielsen (Minerals, 2021)
The Lovozero complex, Kola peninsula, Russia and the Ilímaussaq complex in Southwest Greenland are the largest known layered peralkaline intrusive complexes. Both host world-class deposits rich in REE and other high-tech elements. Both complexes expose spectacular layering with horizons rich in eudialyte group minerals (EGM). We present a detailed study of the composition and cryptic variations in cumulus EGM from Lovozero and a comparison with EGM from Ilímaussaq to further our understanding of peralkaline magma chambers processes. The geochemical signatures of Lovozero and Ilímaussaq EGM are distinct. In Lovozero EGMs are clearly enriched in Na + K, Mn, Ti, Sr and poorer Fe compared to EGM from Ilímaussaq, whereas the contents of ΣREE + Y and Cl are comparable. Ilímaussaq EGMs are depleted in Sr and Eu, which points to plagioclase fractionation and an olivine basaltic parent. The absence of negative Sr and Eu anomalies suggest a melanephelinitic parent for Lovozero. In Lovozero the cumulus EGMs shows decrease in Fe/Mn, Ti, Nb, Sr, Ba and all HREE up the magmatic layering, while REE + Y and Cl contents increase. In Lovozero EGM spectra show only a weak enrichment in LREE relative to HREE. The data demonstrates a systematic stratigraphic variation in major and trace elements compositions of liquidus EGM in the Eudialyte Complex, the latest and uppermost part of Lovozero. The distribution of elements follows a broadly linear trend. Despite intersample variations, the absence of abrupt changes in the trends suggests continuous crystallization and accumulation in the magma chamber. The crystallization was controlled by elemental distribution between EGM and coexisting melt during gravitational accumulation of crystals and/or mushes in a closed system. A different pattern is noted in the Ilimaussaq Complex. The elemental trends have variable steepness up the magmatic succession especially in the uppermost zones of the Complex. The differences between the two complexes are suggested to be related dynamics of the ...